2014
DOI: 10.1016/j.socscimed.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Discussing race-related limitations of genomic testing for colon cancer risk: Implications for education and counseling

Abstract: This study examines communication about limitations of genomic results interpretation for colon cancer risk during education and counseling of minority participants. As part of a larger study conducted from 2010 to 2012, participants recruited from a large primary care clinic were offered testing for a research panel of 3 genomic markers (single nucleotide polymorphisms or SNPs) for colorectal cancer risk. Genetic counselors conducted pre- and post-test sessions which included discussion of limitations of resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Research also suggests that these encounters, and the results of genetic testing, may be experienced as more uncertain for ethnic minority patients given the lack of ethnic diversity within research populations from which genetic data were derived (Butrick et al . ).…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Research also suggests that these encounters, and the results of genetic testing, may be experienced as more uncertain for ethnic minority patients given the lack of ethnic diversity within research populations from which genetic data were derived (Butrick et al . ).…”
Section: Cancer Risk and Responsibilitymentioning
confidence: 97%
“…In the cases of uncertain genetic status, family history and past clinical experience may be drawn on more heavily than numerical (risk) information provided by genetic testing (Aasen and Skolbekken 2014). Research also suggests that these encounters, and the results of genetic testing, may be experienced as more uncertain for ethnic minority patients given the lack of ethnic diversity within research populations from which genetic data were derived (Butrick et al 2014).…”
Section: Individualising Responsibility For Riskmentioning
confidence: 99%
“…Although some researchers explain alternate racial/ethnic classifications based on disparities in experiences with healthcare across racial/ethnic minority groups, this study had an interest in the experiences of all self-identified individuals, regardless of race or ethnicity [44].…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies assessing the process of genetic counseling have reported use of dense, highly technical language by counselors (Butrick et al, ; Kelly et al, ; Roter et al, .). Conveying detailed genetic information is apparently the dominant practice model, one that is unlikely to be effective with many clients, particularly those with lower scientific literacy and formal education attainment (Joseph & Guerra, ; Joseph et al, ).…”
Section: Scientific Endeavorsmentioning
confidence: 99%